Thursday
March 23, 2017

Post a New Question

Posted by on Monday, July 19, 2010 at 6:28pm.

Simplify each trigonometric expression

a) Sin(theta)Cot(theta)-Sin(theta)Cos(theta)

c)(sin x + cos x)(sin x - cos x)+ 2 cos(squared)x

  • Math11U - , Monday, July 19, 2010 at 10:12pm

    sinØcotØ - sinØcosØ
    = sinØcosØ/sinØ - sinØcosØ
    = cosØ - sinØcosØ
    = cosØ(1-sinØ)

    (sin x + cos x)(sin x - cos x)+ 2 cos(squared)x
    = sin^2 x - cos^2 x + 2cos^2 x
    = sin^2x + cos^2x
    = 1

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question